Judge's Assessment of the Statement of a Witness Victim with Mental Retardation in a Rape Case - Astri Wijayanti (Ius Poenale, 2020)
Victim witness testimony in a trial has an important role in proving a case, in this case the judge uses the testimony of a witness with a mental retardation as evidence for witness testimony.  Issues in writing this Journal are How is the judge's assessment of the witness testimony of victims of mental retardation in rape cases? and What principle should be considered by judges in evaluating the testimony of witnesses with mental retardation? This research uses an empirical and normative juridical approach. The results showed that the Judge's evaluation of the testimony of witnesses with mental retardation in a criminal case was essentially independent. Judges can use the testimony of witnesses with mental retardation as evidence of witness testimony by considering the results of research from psychiatric experts who can be academically accounted for to help witnesses with mental retardation to be able to provide information which of course can be verified, the judge can also use it as additional proof or as evidence of instructions if there is compatibility with other valid evidence. The principle that must be considered by judges in evaluating the testimony of witnesses with mental retardation is based on the principles of a fair trial, namely: equality before the law, trials open to the public and conducted orally, competent, independent and impartial courts. Suggestions conveyed by the author in this study Judges must be wise in using existing evidence, especially in cases that are difficult to prove.